A new species of Catasetum (Orchidaceae:Catasetinae) from Casanare, Colombia - Bonilla Morales, Miguel M. (Universidad de Costa Rica, 2017)
Abstract. A new species of Catasetum was found in eastern Colombia, Casanare Department, in the Orinoquía bioregion. The species is described and illustrated, and data associated with its phenology, distribution and conservation status are discussed. The new species, C. lucisuareziae, is related to other species found in the same region, like C. rectangulare and C. callosum, from which it mainly differs by the three-lobed labellum and the presence of two subglobular calli at the base.